La conciliation emploi-famille/vie personnelle chez les infirmières en France et au Québec : une entrée par le groupe professionnel - Nadia Lazzari Dodeler; Diane-Gabrielle Tremblay (Revue Interventions Économiques)
Beyond national specificities, in this research we propose a comparison of perceptions and experiences of nurses, in the public sector, in Québec and in France. We mobilized an analysis based on the profession as a mode of entry to understand the problem of balancing work and family / personal life as well as the measures that could have an impact on the attraction and retention of this workforce.